Incidence and Risk Factors for Acute Kidney Injury in PICU of Dr. Mohammad Hoesin Hospital Palembang - Desti Handayani; Rio Dwi Arliansyah; Indra Saputra; Msy Farah Diba; Hertanti Indah Lestari (Biomedical Journal of Indonesia, 2024)
Introduction. Acute kidney injury (AKI) is a heterogeneous group of conditions characterized by a sudden decrease in the glomerular filtration rate, manifested by an increase in serum creatinine or oliguria. In the Pediatric Intensive Care Unit (PICU), AKI is one of the most common conditions found. Several factors, including age, infection, sepsis, shock, heart disease, mechanical ventilation, and multiple organ failure cause the increase in the incidence of AKI in children. This study aimed to determine the incidence and risk factors for AKI in critically ill children in the PICU of Dr. Mohammad Hoesin Hospital Palembang. Methods. This study was an observational analytic with a cross-sectional design. This study used secondary data based on the medical records of patients treated at the PICU. Critically ill children aged 1-18 years who were treated at the PICU of Dr. Mohammad Hoesin Hospital Palembang in the period of 1 January 2020 to 31 December 2021 were included while existing kidney dysfunction before being admitted to PICU and not fulfilled medical records were excluded to the study. Results. AKI incidence in PICU was 46.7%. There were significant risk factors for AKI which are age (p 0.025), sepsis (p 0.019), shock (p 0.002), mechanical ventilation used (p 0.043), nephrotoxic drugs (p 0.039), and fluid overload (p 0.039). Conclusion. This study found that age, sepsis, shock, mechanical ventilation, nephrotoxic drugs, and fluid overload, were significant risk factors for the incidence of AKI in critically ill children in PICU.